Memperluas Agenda Studi Keamanan Nasional: Politik, Hukum dan Strategi - Simorangkir, Binsar (Universitas Perrtahanan Indonesia (UNHAN), 2020)
National security is the first and foremost responsibility of a nation. A nation isconsidered a strong nation once it is able to secure the livelihood of the people and thewellbeing of the nation itself. Yet the world is evolving quickly and new technologies andinnovations bring about new threats and opportunities towards national security. Thisarticle aims to describe the expansion of politics, laws, and strategies within the study ofnational security. Content analysis method will be used in this article. From more than20 articles referenced here, it can be summarized that changes in strategic environmentis heavily affected by the latest industrial revolution, the industry 4.0. Thus, this bringsabout new challenges such as cyber threats. The researcher then concluded that thesethreats could affect a nation strategically. These threats then focused on political threatsof collective security, current law threats which requires cyber law, and strategic threatswhich is cyber security.Keywords: National Security, Strategy, Politic, Law